Performance Analysis of Karatsuba Multiplication Algorithm for Different Bit Lengths. (3rd July 2015) - Eyupoglu, Can
Abstract: In computer arithmetic, multiplication is one of the most significant operations. Multiplication is used in many operations such as division, squaring and computing reciprocal. In addition, the efficiency of multiplication is crucial due to the use of digital signal processing applications such as correlation, filtering, frequency analysis and image processing. Karatsuba algorithm is one of the algorithms developed for increasing the efficiency and reducing the cost in order to simplify multiplication. In this study, the performance of Karatsuba algorithm is analyzed in terms of the number of multiplication and the total process time for different bit lengths.